Принципи самоорганізації автомобільних транспортних систем - Аулін, В. В.; Голуб, Д. В.; Біліченко, В. В.; Замуренко, А. С.; Aulin, V.; Holub, D.; Bilichenko, V.; Zamurenko, A. (ВНТУ, 2020)
Розглянуто формування принципів безвідмовної роботи автомобільної транспортної системи, наведено її структурну схему та виділено основні поняття. The formation of the principles of trouble-free operation of the road transport system is considered, its structural scheme is given and the basic concepts are highlighted.
Principles of self-organization of automobile transport systems